Support for Children of Parents With Mental Illness: An Analysis of Patients’ Health Records - Kristensen, Kjersti Bergum; Lauritzen, Camilla; Reedtz, Charlotte (Frontiers in Psychiatry, 2022)
Introduction: Children of parents with a mental illness (COPMI) are at risk of behavioral, emotional, and cognitive difficulties and diagnoses. Support and information about parents’ mental illness may contribute to improve their lives, which is the purpose of the intervention Child Talks (CT). This study aimed to investigate the participation rate of CT, characteristics of participating patients and children, and themes in sessions with children. Materials and Methods: Data were collected from 424 electronic patient journals written by healthcare professionals (HCPs) for patients admitted to a clinic for mental health and substance use disorders in the years 2010 – 2015. Both quantitative statistical analysis and qualitative thematic analysis were carried out. Results: Eighteen percent of assessed parents with minor children received the CT intervention and children participated in half of them. Participating children more often knew about their parent’s treatment and condition when initially assessed, and more often lived with the hospitalized parent. Three main themes were identified in sessions with children; communication about parental mental illness within the family, childrens’ struggles, and HCPs’ evaluation of the child’s situation and need for further support. Discussion: Sessions with patients’ children appeared to be relatively rare, and participating children did not necessarily receive appropriate information, support, or follow-up. To ensure that HCPs provide quality support and follow-up to COPMI, the routines and the training of HCPs need to be improved.